Elaine Goodale Eastman, Modernist Author? Re-visiting a Border-crossing Woman Writer’s Place in Literary History - Sarah RUFFING ROBBINS (E-REA)
Elaine Goodale Eastman is not a name generally associated with transnational literary modernism. Yet, a review of her extensive oeuvre demonstrates that her writings interacted in diverse complex ways with that cultural movement. She wrote in a range of genres, including lyric poetry, journalism, didactic children’s books and what she herself termed “potboilers” aimed primarily at supporting her family’s finances. As an editor and co-author with her husband Charles, she contributed to the development of Native American literatures in an intense period of U.S. suppression of indigenous culture—a process in which she played conflicting roles. Through autobiographical texts published late in her life, we see that Eastman continued to have aspirations consistent with a number of modernism’s familiar tenets, even as she also struggled to reconcile the intersectional elements in her gendered personal history with both the successes and the limitations of her multi-faceted publishing career.